Kolektivno dogovarjanje samozaposlenih - kaj prinašajo nove Smernice konkurenčnega prava EU? - Polajžar, Aljoša (Delavci in delodajalci, 2024)
The author discusses the content of the European Commission's Guidelines on the application of the EU competition law to collective agreements concerning the working conditions of solo self-employed persons. The author notes that the 2022 Guidelines further clarify the scope of competition law restrictions on collective bargaining by solo self-employed persons. As a result, the 2022 Guidelines represent a further possible incentive for the various actors (social partners, self-employed persons, legislator, etc.)to proceed further in the development of the field of collective bargaining for solo self-employed persons.
Keywords: collective bargaining; competition law; concept of undertaking; Delovno pravo; economically dependent persons; ekonomsko odvisne osebe; kolektivno dogovarjanje; konkurenčno pravo; pojem podjetja; samozaposlene osebe; self-employed persons